Ki Hajar Dewantara Among System and Its Relevance to Islamic Education - Hanik Afidatur Rofiah; Fauzi Muharom (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The first learning concept based on the Among Ki Hajar Dewantara System, Ing Ngarso Sungtolodo, in front of a civil servant must set an example for students, do assignments and so on. Second, Ing Madya Magun Karsa, in the midst of giving encouragement, a civil servant, apart from giving examples, must give encouragement, enthusiasm for learning, enthusiasm for doing good. Third, Tut Wuri Handayani, the teacher behind gives encouragement, where the tutor is expected to be able to see, discover and understand the talents or potentials that arise and are visible to students. An educator has a big role and a very important role in education, an educator has three roles at once, namely providing an example, facilitator and motifator which are formulated in three sentences in the Among System. At the same time, you must be able to think, feel and behave. The concept of teachings from Ki Hajar Dewantara's perspective is relevant to Islamic religious education. Based on the existing definition, the teaching concept developed by Ki Hadjar Dewantara does not conflict with Islamic education. Only the terms he uses are different, but have the same meaning.